Supporting Students’ Problem Solving Skills Using Science, Technology, Religion, Art, and Mathematics (STREAM) Approach on Sound Wave Concept - Ahmad Suryadi; Fathiah Alatas; Nabila Azka Hanifa (Postgraduate, University of Mataram, 2023)
This study aims to investigate the effect of using science, technology, religion, engineering, art, and mathematics (STREAM) approach on students' problem-solving skills. The study was carried out in physics subjects, especially sound waves. Sixty high school students from one of the senior high schools in Tangerang Province, Indonesia, were divided into two groups to participate in a quasi-experimental study. Each group completed a particular learning sequence in sound wave topics where students in the experimental class carried out learning with the STREAM approach by following the engineering design process while students in the control class used conventional learning. Students' problem-solving skills were measured by eight essay questions. The study revealed that the STREAM approach had a significant effect on students' problem-solving skills (p<0.05). Students' problem-solving skill score in the experimental class was higher than the students' score in the control class. In addition, based on the comparison of the N-Gain values, the increase in the problem-solving skills of the experimental group was higher than that of the control group. The researchers conclude that STREAM is an effective teaching approach that science teachers might also incorporate in their classrooms.